The Influence of Problem Based Learning (PBL) Model on Students Science Skill in Material of Substances and Alteration Changes at Grade IV UPTD SDN Percontohan - Jesi Agustina Panjaitan; Andrino Manalu; Selamat Triadil Saragih (MultiTech Publisher, 2023)
This research aims to determine the influence of the Problem Based Learning (PBL) model on students' science process skills in the form of substances and their changes in class IV UPTD at a pilot state elementary school. The method in this research is the research method used is a type of quantitative research, namely Quasi experimental with a Two Group Pretest-Posttest design. The sampling technique in this research uses Cluster Random Sampling, namely samples taken based on groups. Using the Cluster Random Sampling Technique, from 12 classes, 2 classes were taken which will be given learning treatment using different models, namely class A using the Problem Based Learning (PBL) model and B using conventional methods. The Cluster Random Sampling technique is a regional sampling technique for determining samples if the object to be researched or the data source is very broad, with two research variables: the dependent variable (x) in the form of learning outcomes, and the independent variable (y) in the form of the Problem Based Learning (PBL) model. ) . The data collection technique is the test technique. The test results using the hypothesis testing technique (t test) with the help of the spss program, based on the calculation results, are obtained if Ha: tcount > ttable with a significance level of 0.05 then H0 is rejected and Ha is accepted. tcount 5.147 and ttable 1.697 means 5.147 > 1.697 so that H0 is rejected and Ha is accepted, meaning that there is an influence of the Problem Based Learning (PBL) model on the Science Process Skills (KPS) of students at UPTD SD Negeri Pilot.